Developing a core outcome set for hand fractures and joint injuries in adults: a systematic review. (June 2021) - Deshmukh, Sandeep Rajiv; Mousoulis, Christos; Marson, Ben A.; Grindlay, Douglas; Karantana, Alexia; ,
This study identifies the treatment outcome domains used in recently published studies on the treatment of hand fractures and joint injuries with the aim to inform development of a core outcome set. Seven databases were searched from January 2014 to March 2019 for randomized and quasi-randomized studies and large prospective observational studies. We identified 1777 verbatim outcomes in 160 eligible studies. From the verbatim outcomes we distinguished 639 unique outcomes, which we categorized into 74 outcome domains based on the World Health Organization International Classification of Functioning, Disability, and Health framework. The primary outcome was appropriately identified in only 65% (72/110) of randomized and quasi-randomized controlled trials. Of the 72 studies with a primary outcome identified, 74% (53/72) had an appropriate power calculation. The vast heterogeneity in outcome selection across studies highlights the need for a core outcome set of what outcomes to measure in future clinical research on hand fractures and joint injuries.